Gambaran Activity Of Daily Living pada Pasien Post Operasi Fraktur Femur : Literature Review - Mulia Hakam; Cristina Esria Valentin Tambunan; Jon Hafan Sutawardana; Murtaqib Murtaqib; Kushariyadi Kushariyadi (Poltekkes Kemenkes Mataram, 2023)
ABSTRACTPatients with femoral fractures who have limited range of motion will have difficulty performing ADLs, so they need the help of others. Patients with conditions also require postoperative recovery to restore normal physical, psychological, social, habitual and daily life activities. Therefore, with the prevalence of cases of femur fractures, the importance of the role of nurses in meeting the needs of daily life is important. The research design used was a literature review using 5 database (Proquest, Science Direct, PubMed, Google Scholar, dan Neliti). The process of searching for articles using keyword and Boolen operators (AND, OR, or NOT) aim to define and expand the literature. Of the 10 articles found, the results of the analysis showed that femoral fractures according to their location were femoral head fractures, femoral neck fractures, intertrochanteric fractures, subtrochanteric fractures, femoral shaft fractures, femoral supracondylar/intercondylar fractures (distal femoral fractures). With open, closed and multiple fracture types. And the type of femur fracture surgery is ORIF with several approaches. Activity of Daily Living is an activity that is recommended after surgery to reduce complications and speed up rehabilitation. With several causative factors, namely age, gender, physical health, cognitive abilities, motor skills, perceptual abilities, education, and surgical cases. With several types of daily life activities, namely basic ADL, instrumental ADL, non-vocational ADL. All articles show that people who tend to be older have a higher risk of developing fracture femurcases that inhibition of physical activity that causes disability to death. So it is necessary to expand the scope of information about the importance of activity of daily living so that all people with fracture disease have high vigilance Keywords: Activity of Daily Living, Post Operasi, Femur